PENINGKATAN DAYASAING TANAMAN PANGAN MELALUI AKSELERASI AGROINDUSTRI DAN PEMBERDAYAAN KELEMBAGAAN PERTANIAN - Rooganda Elizabeth (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
Food crops added value is obtained by the process of being processed products through the role of agro-industry. In the era of globalization, Indonesia must immediately implement the development of agro-industries to produce highly competitive trade products and be able to gain global market share. The success of implementing agro-industry is the support and support of the government to increase farmers' income in an effort to realize their welfare. This paper aims to express more comprehensively of food crop-based agro-industry products development acceleration to produce quality processed products, and agricultural functions roles institutions empowerment and high efficiency seriously and sustainably. The acceleration of the implementation of agro-industry is predicted as one of the solutions to efficiency, effectiveness, continuity and the continuity of the trade in processed products rather than raw materials, labor and capital of processed products. It is necessary to increase the competitiveness of Indonesian agroindustry products which have been dominated by raw materials, which only rely on comparative advantages of natural resource abundance and uneducated labor. Obtained agricultural products processed added value that are competitive and meet the high demands of quality and hygiene (GMP), increase in income and welfare of farmers and processed business actors, as well as the transfer of exports of raw materials to processed products. Thanks to the efforts of RMU to process rice into rice, rice flour and crackers (made from rice and rice flour), the RC ratio value of approximately 1.53, 1.28 and 5.91 showed business feasibility and obtained value-added products from processing operations which increased acquisition income. The development and improvement of technological innovations in processed products, investments and HR of business actors is predicted to be able to become the "driving engine" of strong economic progress, especially if the empowerment and institutional development function in line with the development policy programs implemented. Agro-industry products are expected to be able to reach the export market, be able to create jobs and increase interest in young labor in agriculture, able to increase income and the economy in rural areas, and be able to drive the development of rural industrialization.